Preparation Of Activated Carbon From Mangrove Pile Leftover Via Chemical Activation Using Phosphoric Acid For Methylene Blue Adsorption - Lim, Anne Lee (Universiti Sains Malaysia, 2017)
Mangrove pile leftovers which found as wastes at the construction sites were used as the lignocellulosic precursors to prepare activated carbon with high surface area. The main objective of this research was to prepare activated carbons from mangrove pile leftovers via chemical activation using phosphoric acid for the adsorption of methylene blue. The effects of impregnation ratio of phosphoric acid to precursor and activation temperature on the activated carbon yield and the adsorption capacity on methylene blue were investigated. Highest yield of 44.73% was obtained for the activated carbon prepared at impregnation ratio of 3 and activation temperature of 300 ˚C. An impregnation ratio of 5 and activation temperature of 500 ˚C were found to be effective to produce the optimal activated carbon with a yield of 39.13 % and a maximum adsorption capacity of 298.94 mg/g. BET surface area, Langmuir surface area and micropore volume of this activated carbon were 1011.7998 m2/g, 1443.2857 m2/g and 0.091286 cm3/g respectively. Experimental data of methylene blue adsorption for the optimal activated carbon was found to fit well to Freundlich isotherm with correlation coefficient, R2 of 0.9478, indicated that the adsorption of methylene blue on the activated carbon prepared was of multilayer adsorption. The results of adsorption study showed that chemical activation method using phosphoric acid was suitable for developing porous structure in the activated carbon prepared from mangrove pile leftover for the removal of methylene blue from aqueous solution.